Factors influencing treatment success in drug-susceptible tuberculosis patients in Ghana: A prospective cohort study. - Richard Delali Agbeko Djochie; Berko Panyin Anto; Mercy Naa Aduele Opare-Addo; Jonathan Boakye-Yiadom (PLOS Global Public Health)
Optimal rates of positive tuberculosis (TB) treatment outcomes are crucial for patient well-being and preventing the emergence of drug-resistant strains. Unfavourable outcomes present significant challenges to healthcare systems worldwide, making it essential to identify factors that influence treatment success. This study aimed to assess treatment outcomes and explore determinants of success to inform effective interventions and contribute to TB eradication efforts. Patients with active TB were monitored from treatment initiation to completion between January 2021 and December 2021. Data were collected using a Redcap-based tool to capture demographics, adverse reactions to antitubercular medications, and treatment outcomes. Quality of life was assessed using the Short-Form 12 version 2 questionnaire at baseline, the second month, and the sixth month. Logistic regression was performed to analyse associations between participant characteristics and treatment success, with odds ratios indicating the strength of associations at a 0.05 significance level. Among 378 participants, 77.3% achieved successful treatment outcomes, while 13.5% were lost to follow-up, 0.5% experienced treatment failure, and 8.7% died. Key factors influencing treatment success included baseline body weight, weight gain during treatment, HIV status, adverse drug reactions, and mental well-being at treatment initiation. Multivariate analysis revealed that gaining at least 3 kg during treatment and having no risk of depression at baseline significantly increased the likelihood of treatment success.